Figure, Image, Matter. The Material Imagination of Gaston Bachelard - Bertetti , Paolo (E|C, 2023)
Gaston Bachelard is one of the recognized sources of Greimas’ concept of figurativity, whose focus on the sensitive qualities of matter is still one of the main ways for the semiotic study of matter. According to Bachelard, there is an essential relationship between poetic image and material reality: matter is both substance and strength of the image. He uses the term “material imagination” to describe this relationship. However, if the images refer to the material element in their constitution, this does not mean they originate, or rather describe reality; they do not reproduce reality but go beyond it. All the more so, reason images are not the result of a cognitive (and categorizing) activity on reality. Following Bachelard the axes of science and poetry are, in the first instance, opposites. And all that philosophy can hope for is to make science and poetry complementary, to unite them as two well-forged opposites. Poetry, that is subjective, is therefore opposed to objective scientific knowledge.